Effects of the initial fuel temperature on burning behavior of crude oil pool fire in ice cavities. Issue 5 (3rd September 2018) - Kong, Depeng; Zhang, Zhen; Ping, Ping; He, Xu; Yang, Hanbing
ABSTRACT: The influence of the initial fuel temperature on the burning behavior of crude oil pool fire in ice cavities was experimentally studied in this paper. The Bohai crude oil with initial fuel temperatures of 283, 293, and 303 K was burned in an initial ice cavity diameter of 6–8 cm. The mass loss rate exhibits three stages: the initial decrease stage, growth stage, and decay stage. The initial fuel temperature plays a significant role in the initial decrease stage. A heat transfer model is established to predict the mass loss rate, which agrees well with the experimental value.